Density‐matrix renormalization group study of many‐body localization in floquet eigenstates. Issue 7 (31st March 2017) - Zhang, Carolyn; Pollmann, Frank; Sondhi, S. L.; Moessner, Roderich
Abstract : Time‐evolving block decimation and a modified density‐matrix renormalization group [Khemani et al, PRL 2016] is applied to efficiently obtain Floquet eigenstates of one‐dimensional, periodically driven many‐body localized systems. Signatures of many‐body localization such as area‐law entanglement entropy remain robust over a range of parameters. A log‐ arithmic growth of the disorder averaged maximum entanglement entropy indicates the presence of resonant regions. Abstract : We generalize the recently introduced Density‐Matrix Renormalization Group (DMRG‐X) [Khemani et al, PRL 2016] algorithm to obtain Floquet eigenstates of one‐dimensional, periodically driven many‐body localized systems. This generalization is made possible by the fact that the time‐evolution operator for a period can be efficiently represented using a matrix‐product operator. We first benchmark the method by comparing to exact diagonalization for small systems. We then obtain Floquet eigenstates for larger systems and show unambiguously that the characteristic area‐law scaling remains robust.